Income inequality and technological adoption - Santos, S. (2017)
We relate technological adoption (of different technologies) with income inequality. We discovered that some technologies such as aviation, cell phones, electric production, internet, telephone, and TV are skill-complementary in raising inequality. We constructed standardized indexes of skill-complementary technological adoption for modern Information and Communication Technologies (ICT), older ICT, production and transport technologies. We found strong evidence that older ICT and transport technologies (and less frequently modern ICT) tend to increase inequality. Additionally, we discovered that results are much stronger in rich countries than in poor ones. Our results are quite robust to a series of changes in specifications, estimators, samples, and measurement of technology adoption. These results may bring insights to the design of incentive-schemes for technology adoption.